Análise proteômica de células a-549 infectadas por adenovírus espécie f sorotipo 40 (HAdV-40) - Guissoni, Ana Carla Peixoto (2015)
Human adenovirus (HAdVs) are causative agents of different clinical syndromes such as gastroenteritis, respiratory diseases, eye diseases and cystitis. Adenovirus infection can modify the cellular homeostasis through the interaction with the host cell by inducing proteins of several metabolic pathways. The resulting knowledge of this virus-cell interaction may aid the elucidation of the pathogenic mechanisms caused by adenovirus and the host response against viral infection. To study this interaction, a methodology that has been widely used is proteomics, a tool used in this study, which aimed to identify induced proteins due to viral infection. In this context, we used cells A-549 infected with human adenovirus of type F, serotype 40 (HAdV-40). Infected cells and non-infected cells were used for the osmotic lysis, which were quantified by the Bradford method and then digested with trypsin. Peptides were separated on the LC system in two dimensions. The ionization of the peptides was performed by nano-eletronspray source and through analysis of ToF-MSE system aiming the protein identification. A sum of 336 proteins were identified, 206 of them induced and 130 suppressed by the infection with HAdV-40. The main pathways affected by viral infection were: energy, cellular organization, stress response and apoptosis. It was observed alteration of cell metabolism with increase of the glycolytic pathway, β-oxidation and respiratory chain. Also, the results suggest cytoskeleton reorganization and apoptosis induction. The data can to contribute knowledge about adenovirus pathogenesis considering the proteins related to distinct metabolic pathways induced by viral infection.